An Evaluation of the Relative Effectiveness of Function-Based Consequent and Antecedent Interventions in a Preschool Setting. Issue 2 (3rd April 2018) - von Schulz, Jonna H.; Dufrene, Brad A.; LaBrot, Zachary C.; Tingstrom, Daniel H.; Olmi, D. Joe; Radley, Keith; Mitchell, Rachel; Maldonado, Aimee
ABSTRACT: Although there is substantial functional behavioral assessment (FBA) literature suggesting that function-based interventions are effective for improving problem behavior, only a limited number of studies have examined the effectiveness of function-based antecedent versus consequent interventions. Additionally, although there has been a recent increase in the number of studies conducted in the K–12 school setting, only a limited number of studies have included children in the preschool setting. The present study extends existing literature by examining the effectiveness of function-based antecedent versus consequent interventions for reducing problem behavior and increasing appropriately engaged behavior for preschool children without cognitive disabilities. Following an FBA of 4 children, the effectiveness of a function-based antecedent (i.e., noncontingent reinforcement [NCR]) was compared with a function-based consequent (i.e., differential reinforcement of alternative behavior [DRA]) intervention using an alternating treatments design. Results indicated that both function-based NCR and DRA were effective for decreasing problem behavior and increasing appropriately engaged behavior, with function-based NCR being more effective than DRA for 2 of 4 participants.